PENGARUH KETERSEDIAAN PRODUK TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIASI PADA PELANGGAN PT INDO REZA PERKAZA - Mahendra, Reza; Padmalia, Metta (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Abstract. The purpose of this research is to evaluate the effect of product availability on customer loyalty through customer satisfaction for PT Indo Reza Perkaaz customers. The research method used is quantitative research with the sampling method being saturated sampling. The population in this research are all consumers who have purchased scrap material from PT Indo Reza Perkaza, a total of 40 companies. The data collection technique uses a questionnaire. The form of the research questionnaire is a closed questionnaire where respondents answer statements or questions based on the answer choices that have been provided and are measured using a Likert scale. This research uses a multiple linear regression analysis method which is calculated using Smart PLS 4 software. The results of this research show that product availability has a positive effect on customer satisfaction, customer satisfaction does not have effect on customer loyalty, product availability has a positive effect on customer loyalty, and availability products have does not have effect on customer loyalty without directly passing through customer satisfaction.